Influence of Certain Drugs on the Adhesiveness of Human, Rat, and Rabbit Blood Platelets in Vitro - Reber, K; Studer, A (Thrombosis and Haemostasis, 1965)
This is a comparative study of the methods described by H. P. Wright and O’Brien for determining the adhesiveness of thrombocytes. An attempt is made to characterize and statistically correlate both techniques. With the aid of a Coulter Counter for thrombocyte counts, a normal range is presented for human, rat, and rabbit blood. Anticoagulants used are sodium citrate and Heparin.The influence of Cocaine and the Serotonin antagonist Ro 3-0837 was studied on these same substrates, to determine a pharmacological interference with results of either Wright’s test or O’Brien’s. Both drugs are found to induce a statistically significant increase in the “thrombocyte count” as compared to the corresponding controls. These effects are not real but to be attributed to an increase in particle count due to thrombocyte fragmentation as a consequence of drug application. There is no evidence for the claim that these drugs decrease the adhesiveness of thrombocytes.Numerical results of both tests often show a high and statistically significant correlation, especially following the addition of Ro 3-0837. Such is not true of individual blood samples to which no drug has been added. Evidentally, both tests are not specific for the same characteristic of normal blood platelets. But, when Ro 3-0837 is added, the breakdown of unstable platelets is induced; and the corresponding increase in count of thrombocyte fragments is expressed by both tests in the same fashion.